Pengaruh Kepedulian, Pengetahuan, Sikap, Inisiatif Pemerintah, Tekanan Teman Sebaya Dan Spiritualitas Terhadap Niat Beli Produk Ramah Lingkungan Di Banjarmasin - Arafat Alhally (Islamic University of Kalimantan MAB Banjarmasin, 2020)
This study aims to find out and analyze the influence of environment concern, environment knowledge, environmental attitude, government initiative, peer pressure, and spirituality on the purchase intention of environmentally friendly products among consumers in Banjarmasin environment. This research is a research with quantitative approach. The research data are obtained using questionnaires which are distributed to 168 respondents in Banjarmasin. Structural Equation Model (SEM) is a method of data analysis used in this study. The result of this study indicate that environment concern, environment knowledge, environmental attitude, and spirituality have significance influence on purchase intention of environmentally friendly products. While, government initiative and peer pressure have no significance influence on the purchase intention of environmentally friendly products.Keywords : concern, knowledge, spirituality, purchase intention, environmentally friendly products